2022
DOI: 10.1097/ju.0000000000002441
|View full text |Cite
|
Sign up to set email alerts
|

Frailty Is Associated with an Increased Risk of Complications and Need for Repeat Procedures after Sling Surgery in Older Adults

Abstract: Purpose:Sling surgery is the gold standard treatment for stress urinary incontinence in women. While data support the use of sling surgery in younger and middle-aged women, outcomes in older, frail women are largely unknown.Materials and Methods:Data were examined for all Medicare beneficiaries ≥65 years old who underwent sling surgery with or without concomitant prolapse repair from 2014 to 2016. Beneficiaries were stratified using the Claims-Based Frailty Index (CFI) into 4 categories: not frail (CFI <0.15),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…In the setting of an aging population, increased burden will be placed upon providers to decide when to proceed with invasive interventions; the identification of frailty as a prognostic indicator of negative clinical outcomes in patients undergoing urologic procedures is increasingly recognized. 10,11,[15][16][17] Various tests have been used to identify frailty in clinical practice, including simple physical testing, questionnaires, and clinician gross evaluation. 18 Despite multiple clinical practice guidelines for PSA screening stipulating a life-expectancy estimation prior to proceeding with screening, no clear test or method is established to identify this.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the setting of an aging population, increased burden will be placed upon providers to decide when to proceed with invasive interventions; the identification of frailty as a prognostic indicator of negative clinical outcomes in patients undergoing urologic procedures is increasingly recognized. 10,11,[15][16][17] Various tests have been used to identify frailty in clinical practice, including simple physical testing, questionnaires, and clinician gross evaluation. 18 Despite multiple clinical practice guidelines for PSA screening stipulating a life-expectancy estimation prior to proceeding with screening, no clear test or method is established to identify this.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research by Kim et al has shown that a frailty score can be calculated from claims data. 13 Using similar methodology from a prior study, 11 publicly available software was then used to estimate a frailty score for each man in our cohort based on ICD 9/10 codes, CPT codes, and Healthcare Common Procedure Coding System codes. Patients were classified into 2 categories based on level of frailty: frail (CFI ≥0.15) and not frail (CFI <0.15).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study using National Surgical Quality Improvement Program (NSQIP) data showed that frailty-and not age-is associated with major complications of AUS placement and removal procedures [adjusted odds ratio (aOR), 3.5; 95% confidence interval (CI), 1.2-9.9], while another (also using NSQIP data) showed no difference in 30-day complications associated with frailty or increasing comorbidities for artificial urethral sphincter (AUS) or sling (12,18). Frail women undergoing sling procedures have been found to have higher risk of 30-day complications and 1-year mortality (19). Though this study is not directly applicable to the male SUI population, it does highlight the impact of frailty on incontinence procedure outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Van Kuiken et al (page 1276) from San Francisco, California examine the impact of frailty on outcomes of sling surgery for stress urinary incontinence in all Medicare beneficiaries over 65 years of age. 2 They observed that frailty is associated with an increased risk of 30-day complications, need for repeat procedures as well as 1-year mortality. The authors suggest that frailty should be strongly considered for an elderly woman considering the pros and cons of even such a relatively minor surgical procedure.…”
Section: Frailty and Adverse Outcomes After Sling Surgerymentioning
confidence: 99%